Examining the Effect of Alignment of the Rotor of the Emissions Exhaust Fan on Its Operating Parameters - Imrich Vojtko; Petr Baron; Martin Pollák; Jakub Kaščak (Advances in Materials Science and Engineering)
The paper describes research examining the trends in balancing rotary machines and the application of the sequence of steps in execution of the operational balancing of an impeller of the industrial furnace emissions fan. The balancing process is based on the correction of the weight distribution of the body with the given axis of rotation. In trial operation, vibrations (with the measurement of the oscillation phase) were measured on both emission fan rotor bearings. Since the measured vibration value was higher than recommended, it was necessary to take steps to balance the fan’s impeller. The first step of the operational balancing is to identify the initial vibration vector relative to the reference mark, arbitrarily located on the rotating wheel of the fan. In trial operation, the balancing weight mass was changed in the selected balancing level, resulting in the change of the vibration vector compared to the initial state. The size and the angular position of the balancing weight were determined from the vibration values measured. 15 months into operation after the impeller was balanced, the diagnosis of its current technical condition was performed. Total vibrations of the device were measured in the low- and high-frequency range, at four measuring points on the rotor and the drive engine. The measurement confirmed a satisfactory technical condition of the engine and the fan equipment. The effect of balancing has also been demonstrated in the case observed. Reduced bearing wear, elimination of recurrent defects, foundation damage, etc., have been observed.